2014
DOI: 10.1111/iwj.12216
|View full text |Cite
|
Sign up to set email alerts
|

A large Italian observational multicentre study on vascular ulcers of the lower limbs (Studio Ulcere Vascolari)

Abstract: An observational study of 2 years was promoted by the Italian Association for Cutaneous Ulcers (AIUC) in order to monitor the epidemiology of leg ulcers, the trend of healing and the more frequent therapeutic approaches in lower limb ulcers. Fifty-nine sites in 14 different Italian regions involved in the study, with 1333 enrolled patients (1163 patients fully evaluated and followed up for 9 months). A prevalence of females (62%) was observed with a mean age of 70 years and a high rate of hypertension (62%), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 31 publications
1
33
0
2
Order By: Relevance
“…Our group demonstrated that in Germany, the majority of chronic leg ulcers, accounting for almost 65%, were because of an underlying CVI . In the European region, it has been reported that 1% of the Western Europe population is affected with leg venous ulcers, supported by similar statistics in the south of Europe . Summing up these data, we can conclude that in Europe, venous insufficiency is the most common cause of chronic leg ulcers.…”
Section: Discussionsupporting
confidence: 78%
“…Our group demonstrated that in Germany, the majority of chronic leg ulcers, accounting for almost 65%, were because of an underlying CVI . In the European region, it has been reported that 1% of the Western Europe population is affected with leg venous ulcers, supported by similar statistics in the south of Europe . Summing up these data, we can conclude that in Europe, venous insufficiency is the most common cause of chronic leg ulcers.…”
Section: Discussionsupporting
confidence: 78%
“…All participants had ulcers classified by the CEAP classification as C5 or C6. Six studies reported patient comorbidities, which included diabetes mellitus, arterial hypertension, chronic heart failure and cardiovascular disease (Abbade et al., , ; Apollonio et al., ; Legendre et al., ; McDaniel et al., ; Wojcik et al., ). Sample sizes of included studies were generally small with a median size of 84, ranging from 2 to 639.…”
Section: Resultsmentioning
confidence: 99%
“…In eight of the 13 studies reporting weight status, the majority of VLU patients were found to have a BMI >25 (Table ) (Abbade et al., , ; Finlayson et al., ; McDaniel et al., ; Serra et al., ; Tobon et al., ; Vines et al., ; Wojcik et al., ). Of the seven studies that measured obesity exclusively, prevalence ranged from 21.8‐81.8% of participants (Abbade et al., ; Apollonio et al., ; De Franciscis et al., ; Legendre et al., ; McDaniel et al., ; Tobon et al., ; Vines et al., ). Overweight and obesity were found to be related to poor healing of VLUs in three studies (Apollonio et al., ; Labropoulos et al., ; Milic et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess weight and obesity are established independent risk factors for venous ulceration and are associated with delayed VLU healing, yet only 76 studies (just over half of our sample) reported on the BMI of their included patients. The prevalence of obesity (BMI >30) among people with VLU is gaining more attention with one study ( N = 1,163 patients) reporting that 33% had a BMI >30 and a further study reporting 60% of people with VLU being either overweight or obese . When coupled with reduced mobility impacting on activation of the calf muscle pump, clinicians need to take note of this in assisting patients with prevention and reduction of weight gain and determining if an RCT is relevant to the needs of their overweight patients.…”
Section: Discussionmentioning
confidence: 99%